2018
DOI: 10.1902/jop.2017.170328
|View full text |Cite
|
Sign up to set email alerts
|

Non‐surgical model for alveolar bone regeneration by bone morphogenetic protein‐2/7 gene therapy

Abstract: The present findings indicate that a combination of the BMP-2/7 non-viral vector and in vivo electroporation represents a promising non-surgical option for alveolar bone regeneration therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
1
20
1
Order By: Relevance
“…In our previous study, although we found the inflammatory cells until three days in the target site, new bone like tissues were formed on day five after BMP-2/7 gene transfer [11]. Our final goal is to apply our alveolar bone regeneration system for the patients are under the control of the periodontitis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our previous study, although we found the inflammatory cells until three days in the target site, new bone like tissues were formed on day five after BMP-2/7 gene transfer [11]. Our final goal is to apply our alveolar bone regeneration system for the patients are under the control of the periodontitis.…”
Section: Discussionmentioning
confidence: 90%
“…Our final goal is to apply our constructed method clinically for alveolar bone regeneration [10] and to limit new bone formation to the appropriate site. Our previous study revealed that the observation for one week after BMP gene transfer to the periodontal tissues was not enough to evaluate the regenerated alveolar bone [11]. To resolve this problem, we require a suitable and reliable evaluation method to detect regenerated alveolar bone after gene therapy for continuous period of time.…”
Section: Introductionmentioning
confidence: 99%
“…19 Moreover, new alveolar bone tissue was detected in the target site five days after BMP-2/7 gene transfer and was connected with original alveolar bone seven days after gene transfer. The area of osteoid was much wider in periodontal tissue following BMP-2/7 gene transfer than in the control site.…”
Section: Discussionmentioning
confidence: 96%
“…Using all kinds of cell growth factors and combining them with scaffold materials for angiogenesis are among the main reconstruction strategies for supplying blood in artificial bones (Lindhorst, Tavassol, von, et al, ; Lovett et al, ; Sun et al, ). The other main strategies include using transgenic cells to construct bone tissues (Kawai et al, ; Kawai, Bessho, Maruyama, Miyazaki, & Yamamoto, ), using tissues that contain abundant vascular nets and wrapping or implanting them into a bone scaffold material (Li & Kawashita, ; Türer & Önger, ; Wu et al, ), using a drug (gene) release system for the vascularization of artificial bones or bone tissues, and performing vascularized bone tissue preconstruction (Hall, ; Lan, Tian, ZhuGe, et al, ; Moncion, Lin, O'Neill, et al, ). Bioactive artificial bones containing magnetic drug‐carrying microspheres that facilitate vascularization under in vitro magnetic field (SMF or OMF) is currently unreported.…”
Section: Discussionmentioning
confidence: 99%